The Influence Of The Fraud Triangle On Financial Reporting Fraud In Manufacturing Companies Listed On The Indonesia Stock Exchange - Alni Rahmawati; Diyah Islamiyati (Jurnal Ekonomi, 2024)
This study aims to examine the influence of the Fraud Triangle Theory on Financial Statement Fraud. The research approach used is quantitative research, where the variables employed are financial stability, ineffective monitoring, and change in auditor, moderated by an audit committee on fraud. The study was conducted in the manufacturing industry listed on the Indonesia Stock Exchange, utilizing secondary data with a purposive sampling technique. The sample size consists of 144 companies between the years 2019-2022. The analytical tool used is Moderated Regression Analysis (MRA), processed using EViews 12 application. The research findings indicate that financial stability has a positive effect on financial statement fraud, effective monitoring has a negative effect on financial statement fraud, change in auditor has no significant effect on financial statement fraud, and the audit committee as a variable does not moderate financial stability's effect on financial statement fraud. The implications of this research are to enhance transparency in financial reporting so that irregularities in financial statements can be detected, thereby impacting management decision-making. It also raises stakeholders' awareness, including company management, about the dangers of financial fraud, leading to more effective prevention and detection measures that can be implemented within the company.